A high performance processor architecture for multimedia applications. (February 2018) - Khan, Shafqat; Rashid, Muhammad; Javaid, Faraz
Abstract: In this paper, an efficient sub-word parallelism (SWP)-enabled Reduced instruction-set Computer (RISC) architecture is proposed. The proposed architecture can perform efficiently for both conventional and multimedia-oriented applications. Speed-up for multimedia applications is achieved by adding the customized SWP instructions in RISC processor core. Rather than operating on a single data, customized instructions perform parallel computations on multiple pixels, packed in word-size registers. The sub-word-sizes in SWP instructions are selected, based upon the pixel sizes (8, 10, 12, 16-bit) in modern multimedia applications. The SWP-RISC processor is designed and implemented on two different CMOS technology nodes (90 nm and 45 nm). The performance of processor is characterized for different multimedia applications and compared with the state-of-the-art TMS320C64X processor.